2022
DOI: 10.1186/s12284-022-00564-6
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth-Promoting Rhizobacteria Improve Growth, Morph-Physiological Responses, Water Productivity, and Yield of Rice Plants Under Full and Deficit Drip Irrigation

Abstract: Inoculating rice plants by plant growth promoting rhizobacteria (PGPR) may be used as a practical and eco-friendly approach to sustain the growth and yield of drought stressed rice plants. The effect of rice inoculation using plant growth hormones was investigated under drip full irrigation (FI; 100% of evapotranspiration (ETc), and deficit irrigation (DI; 80% of ETc) on growth, physiological responses, yields and water productivities under saline soil (ECe = 6.87 dS m−1) for 2017 and 2018 seasons. Growth (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 77 publications
4
29
0
Order By: Relevance
“…Lysinibacillus fusiformis NE12 and Enterobacter cloaceae NE24 were identified as potential tryptophan-dependent IAA producers in the present work. The similar IAA-producing rice endophytes reported earlier were Serratia marcescens (Ji et al,2014), Ensifer garamanticus (Cardinale et al,2015), Microbacterium laevaniformis (Borah et al,2021), Bacillus megaterium (Abd El-Mageed et al,2022), Flavobacterium sp. (Walitang et al,2017), Herbaspirillum seropedicae, Azorhizobium caulinodans, Rhizobium daejeonense (Liu et al,2022).…”
Section: Growth Hormonessupporting
confidence: 78%
See 1 more Smart Citation
“…Lysinibacillus fusiformis NE12 and Enterobacter cloaceae NE24 were identified as potential tryptophan-dependent IAA producers in the present work. The similar IAA-producing rice endophytes reported earlier were Serratia marcescens (Ji et al,2014), Ensifer garamanticus (Cardinale et al,2015), Microbacterium laevaniformis (Borah et al,2021), Bacillus megaterium (Abd El-Mageed et al,2022), Flavobacterium sp. (Walitang et al,2017), Herbaspirillum seropedicae, Azorhizobium caulinodans, Rhizobium daejeonense (Liu et al,2022).…”
Section: Growth Hormonessupporting
confidence: 78%
“…Borah et al (2021) screened 70 rice endophytes and found Bacillus tequilensis, Microbacterium tesaceum, and M. enclense as potential nitrogen-fixing and mineral solubilizing (P and K) endophytes. Abd El-Mageed et al (2022) found that out of 49 rice endophytes, 16 strains were potential nitrogen-fixers and 36 strains mineral solubilizers. Only a few shared the multiple nutrient-providing traits and authenticated B. megaterium and B. subtilis as potential nutrient-transforming (N, P and K) rice endophytes.…”
Section: Plant Nutrientsmentioning
confidence: 99%
“…In similar studies [26], using Bacillus velezensis as inoculant of C. sativus, it was observed that the host plant modifies the root structure, which improves water and nutrient uptake, promoting a higher photosynthetic rate. It has been suggested that the modification of the root structure of a cucumber plant is related to the phytohormone indoleacetic acid (IAA) produced by S. meliloti, A. radioresistens, and P. paralactis [11,14,27]. In addition, it has been reported that S. meliloti and A. radioresistens possess the ability to fix nitrogen and solubilize phosphate, resulting in an increase on the number of late-stage roots and root hairs, since these elements are essential for the plant to increase photosynthetic pigments and proteins, which improves photosynthetic activity and rate, having a positive effect on plant development and a greater accumulation of biomass [28,29].Furthermore, it has been pointed out that IAA is associated with cell division and differentiation, which improves the structure of the root system [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, beneficial microorganisms have been applied in the plants as a sustainable alternative for food production [11], likewise, the combination with synthetic fertilizers has led to increased plant growth and productivity [7,12]. Plant growth-promoting rhizobacteria (PGPR) are a microorganism group able to increase the shoot and root length, improve water and nutrient absorption, and improve fruit quality and productivity in plants [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently several experimental solutions have been applied to treat the effects of water stress in rice. One effective solution was the use of plant growth promoting rhizobacteria (Abd El-Mageed et al 2022), and foliar spray with organic nutrients i.e. compost tea (Moridi et al 2019).…”
Section: Introductionmentioning
confidence: 99%